PEER EDUCATION AND SUPPORT FOR HEALTHY AGING – A COMMUNITY BASED PARTICIPATORY APPROACH. (16th November 2018) - Rajabali, S; Gartner, S; Hunter, K; Juby, A; Dafoe, W; Wagg, A
Abstract: The number of people aged 65 years and older in the population is on the rise. Older adults, even those with good health, are more likely to have one or more chronic condition(s) and complex physical and social needs. Community Based Participatory Research (CBPR) offers a means to address the needs of older adults and include their perspectives and experiences in the research process. In this paper, we will share the lessons learned by researchers in employing a community based participatory approach in a mixed methods quantitative dominant, stepped-wedge cluster randomized trial that aims to assess the impact of trained peer health coaches on healthy aging behaviours, health literacy and health care seeking in community dwelling seniors. The SHAPES trial engaged seniors' activity centres from the onset in the planning and study design. Drawing upon partnership and feedback from community organizations, a one hour workshop and three facilitated discussion sessions in the areas of healthy brain, healthy heart and healthy bones were developed for delivery to the participants. Based on health coaches' feedback, the modules were modified to include more resources, simplify language and provide clarification where needed. The effects on recruitment and retention, practical constraints, methodological issues and other benefits and challenges of participatory approach involving older adults in the trial are discussed. It is possible to employ community based participatory approaches in robust clinical trials, however, there are certain limitations and challenges of which researchers should be aware and take measures to overcome.